Is a triangle 180 degrees? Using relevant material to explore elementary school students’ reasoning ability - Jihe Chen; Ying Zhou; Tommy Tanu Wijaya; Maximus Tamur (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Students’ proof construction is one of the important abilities in learning mathematical knowledge. To understand the development of Students’ proof construction of the fourth-grade students in Guilin, 15 fourth-grade students were selected to conduct an exploration activity about the sum of the inner angles of a triangle is equal to 180°. Through the observation and interview with students in the activities, we conclude that the reasonable ability of excellent students has coherence and integrity, the middle level students’ proof construction is ordinary and still need to improve, and the Low Students’ proof construction students are weak, and it is difficult to understand the research object. The teacher must have a creative and interesting method to teach students to improve Students’ proof construction from the research process and results.